A life cycle approach to optimizing carbon footprint and costs of a residential building. (October 2017) - Pal, Sudip Kumar; Takano, Atsushi; Alanne, Kari; Siren, Kai
Abstract: Finding life cycle optimized building designs is a challenging task. It requires the inclusion of all phases of the building life cycle in a single optimization problem. The present study demonstrates a life cycle simulation-based optimization approach, by including the operational carbon footprint (OCF) and embodied carbon footprint (ECF) of a building. Particularly, finding and analyzing the difference between life cycle (OCF + ECF) optimized design and operational (only OCF) performance-based optimized design is the primary goal of the current study. The life cycle optimization method is applied to a townhouse in Finland to determine carbon-cost optimal designs. Different options of building envelope insulation thicknesses, window types, heating systems, heat recovery units, and PV area are explored as design variables. It has been found that the heating system is a dominant design variable, which results in clearly separated pareto fronts for each system. Generally, a majority of the design variables' optimal values, obtained from OCF + ECF optimization, suggest thinner insulation for the building envelope and a larger PV area, compared to the optimal solutions from OCF optimization. In a carbon optimal solution, the share of ECF is 39% of the life cycle carbon footprint, whereas in a cost optimal solution, the share of ECF is 28% of the life cycle carbon footprint. Highlights: Both operational and embodied carbon footprint are considered in optimization. Determining the difference between life cycle and operational performance based optimal designs. Life cycle optimization results suggest decreased insulation thickness for building envelope. Among heating systems, GSHP provides the best optimal results for the case study. Carbon and cost-optimal solutions are determined for the case study building.